2006
DOI: 10.4028/www.scientific.net/kem.326-328.661
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Internal Leak in Valve Using Acoustic Emission Method

Abstract: This study is to estimate the feasibility of acoustic emission(AE) method for the internal leak from the valves. In this study, two types of valve(a 4 inch glove steam valve and 4 inch ball water valve) leak tests using three different leak path and various leak rates were performed in order to analyze AE properties when leaks arise in valve seat. As a result of leak test for specimens simulated valve seat, we conformed that leak sound amplitude increased in proportion to the increase of leak rate, and leak ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The results demonstrated that the frequency components related with leakage could be clearly picked up from AE signal with background noise [23]. Lee et al studied the AE characteristics of leakage in two valves (the steam ball valve and water ball valve) under a situation of different leakage modes, and it can be concluded that the leakage rate of valves is directly proportional to the sound amplitude [24]. Recently, the rate of gas leakage of a valve was estimated by the theoretical relationship between the features of AE signals and internal leakage rate of valves [25].…”
Section: The Acoustic Emission (Ae) In Valvesmentioning
confidence: 99%
“…The results demonstrated that the frequency components related with leakage could be clearly picked up from AE signal with background noise [23]. Lee et al studied the AE characteristics of leakage in two valves (the steam ball valve and water ball valve) under a situation of different leakage modes, and it can be concluded that the leakage rate of valves is directly proportional to the sound amplitude [24]. Recently, the rate of gas leakage of a valve was estimated by the theoretical relationship between the features of AE signals and internal leakage rate of valves [25].…”
Section: The Acoustic Emission (Ae) In Valvesmentioning
confidence: 99%
“…Among them, AE technology is based on the principle that the transient elastic wave will be generated when the valve leaks and the AE signal will be sent out. The health state of the valve could be judged by collecting and analysing the valve internal leakage AE signal (VILAES) [4, 5]. As a dynamic detection method, the energy detected by AE technology comes from the measured object itself rather than provided by the detection instruments like ultrasonic and radiographic inspection technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Several kinds of techniques, including acoustic emission (AE) [4], vibration monitoring [5,6] and cavity dynamic pressure [7], have been used for the detection of valve internal leakage. Among these techniques, AE has witnessed a wide application in the detection of valve internal leakage both qualitatively and quantitatively, because it possesses the advantage of nonintrusive, high sensitivity and strong anti-interference ability [8][9][10].…”
Section: Introductionmentioning
confidence: 99%